2016
DOI: 10.18632/oncotarget.10220
|View full text |Cite
|
Sign up to set email alerts
|

miR-153-3p, a new bio-target, is involved in the pathogenesis of acute graft-versus-host disease via inhibition of indoleamine- 2,3-dioxygenase

Abstract: Acute graft-versus-host disease (aGVHD) is a major cause of morbidity and mortality after allogeneic hematopoietic stem cell transplantation. Therefore, seeking reliable biomarkers and delineating the potential biological mechanism are important for optimizing treatment strategies and improving their curative effect. In this study, using a microRNA polymerase chain reaction (PCR)-based chip assay, microRNA-153-3p (miR-153-3p) was screened and selected as a potential biomarker of aGVHD. The elevated plasma miR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 33 publications
0
26
0
Order By: Relevance
“…In contrast to canonical biogenesis of miRs, emerging data supports the findings that miRs can also be stably found in a variety of body fluids, such as saliva ( 70 , 71 ), urine ( 72 ), and blood ( 73 , 74 ) either packaged within exosomes or in complexes with RNA-binding proteins such as Ago or high-density lipoprotein. These miRs, referred to as cell-free miRs ( 75 ), may serve as biomarkers of disease ( 71 , 72 , 74 ) and/or facilitators of disease pathogenesis through cell-to-cell communication ( 75 78 ).…”
Section: Mirs As Tlr Ligandsmentioning
confidence: 99%
“…In contrast to canonical biogenesis of miRs, emerging data supports the findings that miRs can also be stably found in a variety of body fluids, such as saliva ( 70 , 71 ), urine ( 72 ), and blood ( 73 , 74 ) either packaged within exosomes or in complexes with RNA-binding proteins such as Ago or high-density lipoprotein. These miRs, referred to as cell-free miRs ( 75 ), may serve as biomarkers of disease ( 71 , 72 , 74 ) and/or facilitators of disease pathogenesis through cell-to-cell communication ( 75 78 ).…”
Section: Mirs As Tlr Ligandsmentioning
confidence: 99%
“…In mouse models, GvHD biology was functionally linked to several miRs, e.g., miR-155 ( 14 , 15 ), miR-100 ( 16 ), miR-146a ( 17 , 18 ), miR-142 ( 19 ), miR-17-92 ( 20 ), miR-153-3p ( 21 ), and miR-29a ( 22 ).…”
Section: The Role Of Mirs In Myeloid Cells During Graft-versus-host Dmentioning
confidence: 99%
“…There is increasing evidence that serum or plasma miRs could be used as biomarkers and predict acute GvHD onset ( 23 ). A study suggested miR-153-3p as a potential biomarker for GvHD because miR-153-3p plasma levels were elevated on day seven after allo-HCT in the GvHD group compared to the control group even though GvHD had not occurred yet ( 21 ). Through bioinformatics analysis, indoleamine 2,3-dioxygenase (IDO) was found to be a potential target protein of miR-153-3p ( 21 ).…”
Section: The Role Of Mirs In Myeloid Cells During Graft-versus-host Dmentioning
confidence: 99%
See 2 more Smart Citations